2022
DOI: 10.1038/s41467-022-31652-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of Gαob by an adenosine A1 receptor agonist elicits analgesia without cardiorespiratory depression

Abstract: The development of therapeutic agonists for G protein-coupled receptors (GPCRs) is hampered by the propensity of GPCRs to couple to multiple intracellular signalling pathways. This promiscuous coupling leads to numerous downstream cellular effects, some of which are therapeutically undesirable. This is especially the case for adenosine A1 receptors (A1Rs) whose clinical potential is undermined by the sedation and cardiorespiratory depression caused by conventional agonists. We have discovered that the A1R-sele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 156 publications
1
42
0
Order By: Relevance
“…BnOCPA has previously been identified as a high-potency A 1 R-selective full agonist. , Using insights from BnOCPA MD simulations , and with the aim of further improving the A 1 R selectivity and potency, we designed extended BnOCPA derivatives 15 – 18 . Their binding and activity at human A 1 R (hA 1 R) were then explored using both a NanoBRET binding assay and a cAMP accumulation assay, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BnOCPA has previously been identified as a high-potency A 1 R-selective full agonist. , Using insights from BnOCPA MD simulations , and with the aim of further improving the A 1 R selectivity and potency, we designed extended BnOCPA derivatives 15 – 18 . Their binding and activity at human A 1 R (hA 1 R) were then explored using both a NanoBRET binding assay and a cAMP accumulation assay, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…13 Subsequently, we demonstrated that BnOCPA was able to specifically activate Gα ob protein subtype-mediated signaling, which translated into potent in vivo analgesia without causing sedation, bradycardia, hypotension, or respiratory depression. 22 Molecular dynamics (MD) simulations using the cryo-EM structure of the active adenosine-bound A 1 R-heterotrimeric G i2 protein complex (PDB code 6D9H 23 ) proposed four binding modes of BnOCPA 22 due to the high flexibility of the N 6 appended benzyloxy group. 24 Based on these molecular modeling studies, we have designed a series of adenosine-and NECA-based compounds with extended N 6 -benzyloxy-and N 6 -phenoxycyclopentyl substituents (Chart 1) with the aim of improving the potency at A 1 R while maintaining or improving the subtype selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Optimized sensors consisting of Gα-Rluc8 and Gβɣ-GFP2 were developed for all non-visual G proteins, with the exception of G olf and G 14 , and included the first sensors for G 15 and G gust (Olsen et al, 2020). TRUPATH has since been employed to assess the G protein activation profile of a number of GPCRs (Knight et al, 2021; Lieb et al, 2021; Singh, Senatorov, Cheshmehkani, Karmokar, & Moniri, 2022; Voss, Mahardhika, Inoue, & Müller, 2022; Wall et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pleiotropic signalling has been documented for numerous GPCRs (Avet et al, 2022; Hauser et al, 2022; Knight et al, 2021; Lieb et al, 2021; Olsen et al, 2020; Singh et al, 2022; Voss et al, 2022; Wall et al, 2022). Class B1 GPCRs, for example, are classically considered Gα s- coupled GPCRs but have now been demonstrated to consistently exhibit secondary G protein coupling (Wootten et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation